Double cropping and tillage intensity in continuous wheat agroecosystems have variable impacts on soil hydrologic and physical properties - Perejitei E. Bekewe; Joseph A. Burke; Jamie L. Foster; Katie L. Lewis; Haly L. Neely; Clark B. Neely; Lauren E. Tomlin; Brandon Gerrish; Thomas W. Boutton (Soil and Tillage Research, 2026)

Foundation Species Shift Causes a Partial Loss of Functional Support for Benthic Coastal Consumers - Janelle A. Goeke; Thomas W. Boutton; Anna R. Armitage (Estuaries and Coasts, 2024)

Distinct colony boundaries and larval discrimination in polygyne red imported fire ants ( Solenopsis invicta ) - MacKenzie K. Kjeldgaard; Pierre‐André Eyer; Collin C. McMichael; Alison A. Bockoven; Joanie T. King; Ayumi Hyodo; Thomas W. Boutton; Edward L. Vargo; Micky D. Eubanks (Molecular Ecology, 2022)
Evaluating the factors that promote invasive ant abundance is critical to assess their ecological impact and inform their management. Many invasive ant species show reduced nestmate recognition and an absence of boundaries between unrelated nests, which allow populations to achieve greater densities due to reduced intraspecific competition. We examined nestmate discrimination and colony boundaries in introduced populations of the red imported fire ant ( Solenopsis invicta ; hereafter, fire ant). Fire ants occur in two social forms: monogyne (colonies with a single egg‐laying queen) and polygyne (colonies with multiple egg‐laying queens). In contrast with monogyne nests, polygyne nests are thought to be interconnected due to the reduced antagonism between non‐nestmate polygyne workers, perhaps because polygyne workers habituate the colony to an odour unique to Gp ‐ 9 b ‐carrying adults. However, colony boundaries and nestmate discrimination are poorly documented, particularly for worker‐brood interactions. To delimit boundaries between field colonies, we correlated the exchange of a 15 N‐glycine tracer dissolved in a sucrose solution with social form. We also evaluated nestmate discrimination between polygyne workers and larvae in the laboratory. Counter to our expectations, polygyne colonies behaved identically to monogyne colonies, suggesting both social forms maintain strict colony boundaries. Polygyne workers also preferentially fed larval nestmates and may have selectively cannibalized non‐nestmates. The levels of relatedness among workers in polygyne colonies was higher than those previously reported in North America (mean ± standard error: 0.269 ± 0.037). Our study highlights the importance of combining genetic analyses with direct quantification of resource exchange to better understand the factors influencing ant invasions.

Root density distribution and biomass allocation of co-occurring woody plants on contrasting soils in a subtropical savanna parkland - Yong Zhou; Stephen E. Watts; Thomas W. Boutton; Steven R. Archer (Plant and Soil, 2019)

Soil phosphorus does not keep pace with soil carbon and nitrogen accumulation following woody encroachment - Yong Zhou; Thomas W. Boutton; X. Ben Wu (Global Change Biology, 2018)
Soil carbon, nitrogen, and phosphorus cycles are strongly interlinked and controlled through biological processes, and the phosphorus cycle is further controlled through geochemical processes. In dryland ecosystems, woody encroachment often modifies soil carbon, nitrogen, and phosphorus stores, although it remains unknown if these three elements change proportionally in response to this vegetation change. We evaluated proportional changes and spatial patterns of soil organic carbon ( SOC ), total nitrogen ( TN ), and total phosphorus ( TP ) concentrations following woody encroachment by taking spatially explicit soil cores to a depth of 1.2 m across a subtropical savanna landscape which has undergone encroachment by Prosopis glandulosa (an N 2 fixer) and other woody species during the past century in southern Texas, USA . SOC and TN were coupled with respect to increasing magnitudes and spatial patterns throughout the soil profile following woody encroachment, while TP increased slower than SOC and TN in topmost surface soils (0–5 cm) but faster in subsurface soils (15–120 cm). Spatial patterns of TP strongly resembled those of vegetation cover throughout the soil profile, but differed from those of SOC and TN , especially in subsurface soils. The encroachment of woody species dominated by N 2 ‐fixing trees into this P‐limited ecosystem resulted in the accumulation of proportionally less soil P compared to C and N in surface soils; however, proportionally more P accrued in deeper portions of the soil profile beneath woody patches where alkaline soil pH and high carbonate concentrations would favor precipitation of P as relatively insoluble calcium phosphates. This imbalanced relationship highlights that the relative importance of biotic vs. abiotic mechanisms controlling C and N vs. P accumulation following vegetation change may vary with depth. Our findings suggest that efforts to incorporate effects of land cover changes into coupled climate–biogeochemical models should attempt to represent C‐N‐P imbalances that may arise following vegetation change.

Rooting strategies in a subtropical savanna: a landscape-scale three-dimensional assessment - Yong Zhou; Thomas W. Boutton; X. Ben Wu; Cynthia L. Wright; Anais L. Dion (Oecologia, 2018)

Woody plant encroachment amplifies spatial heterogeneity of soil phosphorus to considerable depth - Yong Zhou; Thomas W. Boutton; X. Ben Wu (Ecology, 2018)
The geographically extensive phenomenon of woody plant encroachment into grass‐dominated ecosystems has strong potential to influence biogeochemical cycles at ecosystem to global scales. Previous research has focused almost exclusively on quantifying pool sizes and flux rates of soil carbon and nitrogen (N), while few studies have examined the impact of woody encroachment on soil phosphorus (P) cycling. Moreover, little is known regarding the impact of woody encroachment on the depth distribution of soil total P at the landscape scale. We quantified patterns of spatial heterogeneity in soil total P along a soil profile by taking spatially explicit soil cores to a depth of 120 cm across a subtropical savanna landscape that has undergone encroachment by Prosopis glandulosa (an N 2 ‐fixer) and other tree/shrub species during the past century. Soil total P increased significantly following woody encroachment throughout the entire 120‐cm soil profile. Large groves (>100 m 2 ) and small discrete clusters ( 2 ) accumulated 53 and 10 g P/m 2 more soil P, respectively, compared to grasslands. This P accumulation in soils beneath woody patches is most likely attributable to P uplift by roots located deep in the soil profile (>120 cm) and transfer to upper portions of the profile via litterfall and root turnover. Woody encroachment also altered patterns of spatial heterogeneity in soil total P in the horizontal plane, with highest values at the centers of woody patches, decreasing toward the edges, and reaching lowest values in the surrounding grassland matrix. These spatial patterns were evident throughout the upper 1.2 m of the soil profile, albeit at reduced magnitude deeper in the soil profile. Spatial generalized least squares models indicated that fine root biomass explained a significant proportion of the variation in soil total P both across the landscape and throughout the profile. Our findings suggest that transfer of P from deeper soil layers enlarges the P pool in upper soil layers where it is more actively cycled may be a potential strategy for encroaching woody species to satisfy their P demands.

Quantifying soil organic carbon in complex landscapes: an example of grassland undergoing encroachment of woody plants - FENG LIU; X. BEN WU; E. BAI; THOMAS W. BOUTTON; STEVEN R. ARCHER (Global Change Biology, 2011)
The invasion of woody plants into grass‐dominated ecosystems has occurred worldwide during the past century with potentially significant impacts on soil organic carbon (SOC) storage, ecosystem carbon sequestration and global climate warming. To date, most studies of tree and shrub encroachment impacts on SOC have been conducted at small scales and results are equivocal. To quantify the effects of woody plant proliferation on SOC at broad spatial scales and to potentially resolve inconsistencies reported from studies conducted at fine spatial scales, information regarding spatial variability and uncertainty of SOC is essential. We used sequential indicator simulation (SIS) to quantify spatial uncertainty of SOC in a grassland undergoing shrub encroachment in the Southern Great Plains, USA. Results showed that both SOC pool size and its spatial uncertainty increased with the development of woody communities in grasslands. Higher uncertainty of SOC in new shrub‐dominated communities may be the result of their relatively recent development, their more complex above‐ and belowground architecture, stronger within‐community gradients, and a greater degree of faunal disturbance. Simulations of alternative sampling designs demonstrated the effects of spatial uncertainty on the accuracy of SOC estimates and enabled us to evaluate the efficiency of sampling strategies aimed at quantifying landscape‐scale SOC pools. An approach combining stratified random sampling with unequal point densities and transect sampling of landscape elements exhibiting strong internal gradients yielded the best estimates. Complete random sampling was less effective and required much higher sampling densities. Results provide novel insights into spatial uncertainty of SOC and its effects on estimates of carbon sequestration in terrestrial ecosystem and suggest effective protocol for the estimating of soil attributes in landscapes with complex vegetation patterns.

Spatial scaling of ecosystem C and N in a subtropical savanna landscape - FENG LIU; X. BEN WU; E. BAI; THOMAS W. BOUTTON; STEVEN R. ARCHER (Global Change Biology, 2010)
Widely occurred woody encroachment in grass‐dominated ecosystems has the potential to influence soil organic carbon (SOC) and total nitrogen (TN) pools at local, regional, and global scales. Evaluation of this potential requires assessment of both pool sizes and their spatial patterns. We quantified SOC and TN, their relationships with soil and vegetation attributes, and their spatial scaling along a catena (hill‐slope) gradient in the southern Great Plains, USA where woody cover has increased substantially over the past 100 years. Quadrat variance analysis revealed spatial variation in SOC and TN at two scales. The larger scale variation (40–45 m) was approximately the distance between centers of woody plant communities and their adjoining herbaceous patches. The smaller scale variation (10 m) appeared to reflect the local influence of shrubs on SOC and TN. Litter, root biomass, shrub, and tree basal area (a proxy for plant age) exhibited not only similar spatial scales, but also strong correlations with SOC and TN, suggesting invasive woody plants alter both the storage and spatial scaling of SOC and TN through ecological processes related primarily to root turnover and, to a lesser extent litter production, as mediated by time of occupancy. Forb and grass biomass were not significantly correlated with SOC and TN suggesting that changes in herbaceous vegetation have not been the driving force for the observed changes in SOC and TN. Because SOC and TN varied at two scales, it would be inappropriate to estimate SOC and TN pools at broad scales by extrapolating from point sampling at fine scales. Sampling designs that capture variation at multiple scales are required to estimate SOC and TN pools at broader scales. Knowledge of spatial scaling and correlations will be necessary to design field sampling protocols to quantify the biogeochemical consequences of woody plant encroachment at broad scales.

Spatial variation of the stable nitrogen isotope ratio of woody plants along a topoedaphic gradient in a subtropical savanna - Edith Bai; Thomas W. Boutton; Feng Liu; X. Ben Wu; Steven R. Archer; C. Thomas Hallmark (Oecologia, 2009)

Variation in woody plant δ13C along a topoedaphic gradient in a subtropical savanna parkland - Edith Bai; Thomas W. Boutton; Feng Liu; X. Ben Wu; Steven R. Archer (Oecologia, 2008)

Grazing and Ecosystem Carbon Storage in the North American Great Plains - Justin D. Derner; Thomas W. Boutton; David D. Briske (Plant and Soil, 2006)

Elevated atmospheric carbon dioxide increases soil carbon - JULIE D. JASTROW; R. MICHAEL MILLER; ROSER MATAMALA; RICHARD J. NORBY; THOMAS W. BOUTTON; CHARLES W. RICE; CLENTON E. OWENSBY (Global Change Biology, 2005)
The general lack of significant changes in mineral soil C stocks during CO 2 ‐enrichment experiments has cast doubt on predictions that increased soil C can partially offset rising atmospheric CO 2 concentrations. Here, we show, through meta‐analysis techniques, that these experiments collectively exhibited a 5.6% increase in soil C over 2–9 years, at a median rate of 19 g C m −2 yr −1 . We also measured C accrual in deciduous forest and grassland soils, at rates exceeding 40 g C m −2 yr −1 for 5–8 years, because both systems responded to CO 2 enrichment with large increases in root production. Even though native C stocks were relatively large, over half of the accrued C at both sites was incorporated into microaggregates, which protect C and increase its longevity. Our data, in combination with the meta‐analysis, demonstrate the potential for mineral soils in diverse temperate ecosystems to store additional C in response to CO 2 enrichment.

Above‐ and below‐ground responses of C 3 –C 4 species mixtures to elevated CO 2 and soil water availability - JUSTIN D. DERNER; HYRUM B. JOHNSON; BRUCE A. KIMBALL; PAUL J. PINTER; H. Wayne POLLEY; CHARLES R. TISCHLER; THOMAS W. BOUTTON; ROBERT L. LAMORTE; GERALD W. WALL; NEIL R. ADAM; STEVEN W. LEAVITT; MICHAEL J. OTTMAN; et al. (Global Change Biology, 2003)
We evaluated the influences of CO 2 [Control, ∼ 370 µ mol mol − 1 ; 200 µ mol mol − 1 above ambient applied by free‐air CO 2 enrichment (FACE)] and soil water (Wet, Dry) on above‐ and below‐ground responses of C 3 (cotton, G ossypium hirsutum ) and C 4 (sorghum, Sorghum bicolor ) plants in monocultures and two density mixtures. In monocultures, CO 2 enrichment increased height, leaf area, above‐ground biomass and reproductive output of cotton, but not sorghum, and was independent of soil water treatment. In mixtures, cotton, but not sorghum, above‐ground biomass and height were generally reduced compared to monocultures, across both CO 2 and soil water treatments. Density did not affect individual plant responses of either cotton or sorghum across the other treatments. Total (cotton + sorghum) leaf area and above‐ground biomass in low‐density mixtures were similar between CO 2 treatments, but increased by 17–21% with FACE in high‐density mixtures, due to a 121% enhancement of cotton leaf area and a 276% increase in biomass under the FACE treatment. Total root biomass in the upper 1.2 m of the soil was not influenced by CO 2 or by soil water in monoculture or mixtures; however, under dry conditions we observed significantly more roots at lower soil depths ( > 45 cm). Sorghum roots comprised 81–85% of the total roots in the low‐density mixture and 58–73% in the high‐density mixture. CO 2 ‐enrichment partly offset negative effects of interspecific competition on cotton in both low‐ and high‐density mixtures by increasing above‐ground biomass, with a greater relative increase in the high‐density mixture. As a consequence, CO 2 ‐enrichment increased total above‐ground yield of the mixture at high density. Individual plant responses to CO 2 enrichment in global change models that evaluate mixed plant communities should be adjusted to incorporate feedbacks for interspecific competition. Future field studies in natural ecosystems should address the role that a CO 2 ‐mediated increase in C 3 growth may have on subsequent vegetation change.